Lipid Extract From a Vegetable (Sonchus Oleraceus) Attenuates Adipogenesis and High Fat Diet-Induced Obesity Associated With AMPK Activation - Chen, Chih-Yu; Su, Chien-Wen; Li, Xiangyong; Liu, Yinghua; Pan, Qian; Cao, Tinglan; Kang, Jing X. (Frontiers in Nutrition, 2021)
Scope Sonchus Oleraceus, named bitter vegetable (BV), has been known to have multiple health benefits such as anti-aging and anti-inflammation. However, the role of BV in the prevention of obesity is unclear. The aim of this study was to examine the effect of BV lipid extracts (BVL) on obesity development. Methods and Results Following treatments of high fat diet-induced obese mice (C57BL/6J) with BVL (10 mg/30 g of mouse/day) for a month, mice exhibited a significant reduction in weight gain, blood triglyceride, and fasting blood glucose compared to control mice. Intriguingly, phosphorylated AMPK, a key regulator of nutrient metabolism, was markedly increased in inguinal fat of BVL group. In 3T3-L1 cells, BVL-7 (100 µg/ml), an omega-3 fatty acid-rich fraction from BVL, lowered lipid accumulation and down-regulated the gene expression of adipocyte markers. The inhibitory effect of BVL occurred at the early stage of adipocyte differentiation, leading to the delay of mitotic clonal expansion. AMPK knockdown by siRNA abolished the inhibitory effect of BVL-7 on adipogenesis, suggesting that AMPK is essential for BVL-regulated adipocyte differentiation. Conclusion BVL can effectively inhibit adipogenesis through, at least in part, stimulating AMPK pathway and attenuate HFD-induced obesity. Our findings suggest that BVL can be a promising dietary supplement for protection against obesity, and the effective component of BVL can be potentially developed for anti-obesity drugs.